Clinical Trials in Vulnerable Populations - Prostran, Milica (IntechOpen, 2018)
This book Clinical Trials in Vulnerable Populations has 12 chapters divided into 4 sections: Minority Patients, Women, Medically Compromised Patients and Clinical Trials. Contributing authors came from several countries, from Serbia to Turkey. The book was edited by Professor Milica Prostran MD, Ph.D., specialist in Clinical Pharmacology. The potential reader is shown a modern approach to clinical trials in vulnerable populations, from different points of view. The chapters deal at length and clarity with their topics. Finally, I believe, that this book I edited and reviewed with dedication will capture the attention of many readers, from medical students to practicing doctors and pharmacists. All of whom must consider this very important field of medicine: clinical trials in vulnerable patients.